Restaurant Liquid Waste Treatment into Clean Water Using Graded Filter-Ultrafiltration Membrane Polyethersulfone (PES) Method - Fadhilah, Intan; Hamdan, Abd Mujahid; Razi, Fachrul (Politeknik Negeri Malang, 2023)
Restaurant liquid waste contains elevated pollutant levels and is commonly discharged directly into the environment, leading to adverse impacts on ecosystems and aquatic life. The traditional methods for processing such wastewater often involve extensive land usage and complicated operations, posing challenges for effective treatment. Therefore, there is a need for a more practical technology to manage restaurant liquid waste, and one promising approach is the utilization of membrane technology for wastewater treatment. In this study, the researchers employed a combination process of multilevel filters with downflow flow and PES membrane ultrafiltration to treat the restaurant liquid waste. The multilevel filter comprised several layers of filter media, including silica sand, activated carbon, zeolite, and gravel, with specific thicknesses on a PVC pipe. For the PES membrane, two different concentrations were tested: 15% and 20% PES. To evaluate the efficiency of the treatment process, pollutant parameters such as pH, TSS (Total Suspended Solids), COD (Chemical Oxygen Demand), and turbidity were measured. The results indicated significant pollutant reduction: pH levels could reach 6.9, TSS degradation achieved up to 98.37%, COD degradation up to 88.14%, and turbidity degradation up to 97.03%. Based on the outcomes, the most effective treatment for converting restaurant wastewater into clean water involved the combined use of multilevel filters and a 20% PES membrane ultrafiltration system.